2011
DOI: 10.3164/jcbn.10-110
|View full text |Cite
|
Sign up to set email alerts
|

Polished rice as natural sources of cancer-preventing geranylgeranoic acid

Abstract: Geranylgeranoic acid, a 20-carbon polyprenoic acid (all-trans 3,7,11,15-tetramethyl-2,4,6,10,14-hexadecatetraenoic acid) and its derivatives were previously developed as synthetic “acyclic retinoids” for cancer chemoprevention. Recently, we demonstrated the natural occurrence of geranylgeranoic acid in various medicinal herbs (Shidoji and Ogawa, 2004). In this present study, we present several lines of evidence to demonstrate that geranylgeranyl diphosphate taken in foods could be metabolized to GGA through ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Consistently, Holstein et al (41) reported that the FPP levels were higher than the geranyl diphosphate levels in human myeloma cell lines. Taken together with our previous reports (26,27), we propose a possible metabolic flow from MVA to GGA in Fig. 7, where GGOH, a dephosphorylated form of GGPP by GGPP pyrophosphatase (25), is enzymatically oxidized by using molecular oxygen to GGal (26), which is further oxidized to GGA in a NAD-dependent manner (26,27).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistently, Holstein et al (41) reported that the FPP levels were higher than the geranyl diphosphate levels in human myeloma cell lines. Taken together with our previous reports (26,27), we propose a possible metabolic flow from MVA to GGA in Fig. 7, where GGOH, a dephosphorylated form of GGPP by GGPP pyrophosphatase (25), is enzymatically oxidized by using molecular oxygen to GGal (26), which is further oxidized to GGA in a NAD-dependent manner (26,27).…”
Section: Discussionsupporting
confidence: 83%
“…Once geranylgeraniol (GGOH) is produced through dephosphorylation of GGPP by the specific diphosphatase, it seems reasonable to assume that the nonspecific fatty alcohol dehydrogenase-fatty aldehyde dehydrogenase system might produce GGA through an intermediate of geranylgeranial (GGal). However, we found that the first oxidation reaction from GGOH to GGal did not require NAD + , but requires molecular oxygen, at least in a cell-free system of either HuH-7 cell lysates (26) or rat liver homogenates (27). At present, the GGA biosynthetic pathway from GGOH is not yet clear, but we have preliminarily reported the natural existence of endogenous GGA in human hepatoma HuH-7 cells (26) and also in blood serum from healthy young volunteers (28) using LC/MS.…”
mentioning
confidence: 80%
“…We assigned the latter peak as GGal, because authentic or freshly prepared GGal eluted at 27.5 min corresponding to the latter peak, but aged GGal preparation yielded additional 26.5-min peak. These two peaks were also previously detected on a HPLC chromatogram of UV absorption at 250 nm with rat liver homogenates (14). When NAD was removed from the reaction mixture, to our surprise, both peak areas increased (Fig.…”
Section: Enzymatic Conversion From Ggoh To Ggal In a Cell-free Systemmentioning
confidence: 70%
“…Based upon its chemical structure, we reasonably assumed that cancer-preventive GGA could be enzymatically derived from GGOH, which is a common precursor of all natural diterpenoids hydrolyzed from GGPP by a specific pyrophosphatase enzyme (2,12). We have also reported that bovine intestinal alkaline phosphatase releases GGOH from GGPP (14). We wished to know whether GGOH is oxidized to GGA in human cells, because GGA has been shown to be a biologically active compound that can induce cell death in human hepatoma cells (16).…”
Section: Preparation Of Lipid Extracts From Huh-7 Cellsmentioning
confidence: 99%
“…Geranylgeraniol (GGOH) is a C20 isoprenoid found in fruits, vegetables, and grains, including rice. As a food substance, GGOH is categorized as 'Generally Recognized as Safe' (8). GGOH is an intermediate product in the mevalonate pathway and acts as a precursor to geranylgeranylpyrophosphate (GGPP).…”
mentioning
confidence: 99%